The Shield of Resilience: Mediating the Effects of Internet Addiction on Adolescent Anger Control - İnci Bakan Kıraç; Aida Sahmurova; Mirko Duradoni; Andrea Guazzini; Mustafa Can Gursesli (Advances in Public Health)
Adolescence is a crucial developmental period characterized by physical, emotional, and social changes. This makes adolescents particularly vulnerable to various stressors, including Internet addiction. The increasing prevalence of Internet use has brought new challenges, as excessive and uncontrolled engagement with digital platforms, often referred to as Internet addiction, can disrupt emotional regulation and increase behavioral difficulties. Anger control, an important component of emotional wellbeing at this stage, is particularly affected by Internet addiction and can lead to aggressive tendencies and long-term emotional problems. This study examines the mediating role of psychological resilience in the relationship between Internet addiction and anger control among adolescents between the ages of 12 and 14. A total of 406 students, selected using convenience sampling, participated in the study. Data were collected from the Internet Addiction Test (IAT), the Trait Anger and Anger Expression (T-Anger and AngerEX) scale, and the Child and Youth Resilience Measure (CYRM-12). Statistical analyses, including regression and mediation analyses, were conducted using the PROCESS macro in SPSS with 5000 bootstrap samples. The results show a significant negative relationship between Internet addiction and both psychological resilience and anger control, with Internet addiction explaining 20.2% of the variance in resilience and 11.5% in anger control. In addition, psychological resilience partially mediated the relationship between Internet addiction on anger control, explaining 25.1% of the variance. These findings highlight the importance of enhancing psychological resilience as a protective factor to mitigate the negative impact of Internet addiction on adolescents’ emotional regulation.